The Metaphysics of Wind and Willows in drama dialogy - Lazdynas, Gintaras (Respectus Philologicus, 2001)
Algirdas Landsbergis tries to conform intellectual origin and mathematically precise construction of text in drama dilogy with the philosophically artistic completion of the world and the concept of style. However, this attempt is fruitless: it provides us with the impression of a mechanically completed construction, which lacks the energy of artistic information. The works have no interior or exterior, empirical or spiritual cosmic identity. When this happens, the content of unconscious "depth" doesn’t reach the heights of metaphysics. Thus, it becomes a code of elementary moral norms, which controls the streams of one’s psyche. In his drama dilogy A. Landsbergis demonstrates a usual situation for the Lithuanian literature: Lithuanian authors most often deal with the metaphysical revelations unsuccessfully, because once they start talking about Being, they slip into a discussion about the modes of life.